Palaeoenvironmental Reconstruction of the Puerto Madryn Formation (Middle to Late Miocene), Northeast of Patagonia: Palynology, Nannofossils and Stratigraphy - Fuentes, Sabrina Natalia; Cuitiño, José Ignacio; Martz, Paula Anabela; Perez Panera, Juan Pablo; Guler, Maria Veronica; Palazzesi, Luis; Barreda, Viviana Dora; Scasso, Roberto Adrian
A 20 m-thick interval of the Puerto Madryn Formation was the subject of a multiproxy study, including sedimentological and stratigraphical observations as well as marine-derived amorphous organic matter, phytoclast, palynomorphs and calcareous nannofossils assessments. Three palynofacies were defined based on qualitative and quantitative analysis of the palynological organic matter that contributed to the palaeoenvironment inferences. Based on their sedimentology, palynology and calcareous nannofossils, the section was divided into four intervals: Interval 1 accumulated in relatively stable, warm water conditions, without salinity fluctuations, in an inner shelf; Intervals 2 and 3 show a marked upward fining trend and a progressive change towards a phytoclast-dominated palynofacies; Interval 4, which represents a reinstauration of normal marine conditions with a regressive trend. The accumulation of the finest-grained deposits on the shelf corresponds to the most continental signature of the succession which seems to contradict the classic grain-size stratigraphic trends for shallow marine sedimentary successions. We interpret this deposit as the result of the progressive increase of fluvial, mud-laden freshwater input into the depositional system produced by switching of deltaic channels processes. The dinocyst assemblages reflect overall warm-water conditions. Nevertheless, the presence of cool-water indicator species in some levels suggests the influence of Antarctic cold-waters. The diagnostic dinocyst and nannofossil taxa support the age of the studied interval as Serravalian-Tortonian. Se estudió un intervalo de 20 m de exposición de la Formación Puerto Madryn mediante un enfoque multiproxy que incluye observaciones sedimentológicas y estratigráficas y la determinación de materia orgánica, fitoclastos, palinomorfos y nanofósiles calcáreos. Se definieron tres palinofacies basadas en el análisis cuali- y cuantitativo de la materia orgánica que contribuyeron a inferir las condiciones paleoambientales. ...